ERK phosphorylation as a marker of RAS activity and its prognostic value in non-small cell lung cancer. (November 2020) - Reissig, Timm M.; Sara, Linda; Ting, Saskia; Reis, Henning; Metzenmacher, Martin; Eberhardt, Wilfried E.E.; Zaun, Gregor; Herold, Thomas; Aigner, Clemens; Darwiche, Kaid; Stuschke, Martin; Schildhaus, Hans-Ulrich; et al.
Highlights: High p-ERK levels associate with a trend towards worse survival in advanced NSCLC. p-ERK may serve as an indicator of RAS activity and biomarker for immunotherapy. p-AKT was not found to serve as prognosticator for survival. Abstract: Background: Deregulated signal transduction pathways play a key role in development, progression and therapeutic resistance of non-small cell lung cancers (NSCLC). The purpose of this study is to assess the downstream markers of two well-characterized pathways and to correlate them with clinical outcome. Design: 670 patients with metastatic NSCLC were prospectively enrolled in a comprehensive biomarker profiling program at a single center from 2012 to 2016. Phosphorylation of extracellular signal-regulated kinase (p-ERK), and protein kinase B (p-AKT) was assessed by standardized immunohistochemistry. Product of scores for quantity and quality of staining were calculated (immunoreactive score, 0–9). Somatic mutations of Kirsten rat sarcoma viral oncogene homolog [KRAS], epithelial growth factor receptor [EGFR], v-Raf murine sarcoma viral oncogene homolog B [BRAF] and phosphatidylinositol 3-kinase [PIK3CA]) were detected by Sanger (2012-03/2015) and amplicon NGS (04/2015-02/2016). Patients enrolled during the first year (2012) were used as discovery cohort. Patients enrolled from 2013 to 02/2016 were used as validation cohort. Clinical data were retrieved from the electronic medical records and were analyzed retrospectively. Results: Using a discovery cohort, we identified an immunoreactive score of p-ERK ≥3 to be prognostically relevant. The validation cohort confirmed that higher levels of p-ERK correlated with worse overall survival (OS) and higher proportion of RAS mutations. Multivariate analysis including established risk factors such EGFR, ALK or ROS mutations and metastatic disease showed a trend of a detrimental effect of high p-ERK on OS (HR 1.23, CI 0.94–1.59, p = 0.131 for p-ERK immunoreactive score ≥3) and time to treatment failure after first-line therapy in the validation cohort. Phosphorylated AKT did not correlate with clinical outcome. Conclusion: While serving as a prognosticator in univariate analysis, highly phosphorylated ERK does not convey a significant prognostic effect for OS in the presence of other prognostic factors. Phosphorylated ERK indicates a higher activity of RAS in advanced NSCLC.